A review of climate-change impact and adaptation studies for the water sector in Thailand. (2nd February 2021) - Kiguchi, Masashi; Takata, Kumiko; Hanasaki, Naota; Archevarahuprok, Boonlert; Champathong, Adisorn; Ikoma, Eiji; Jaikaeo, Chaiporn; Kaewrueng, Sudsaisin; Kanae, Shinjiro; Kazama, So; Kuraji, Koichiro; Matsumoto, Kyoko; et al.
Abstract: Thailand plays a central economic and policy-making role in Southeast Asia. Although climate change adaptation is being mainstreamed in Thailand, a well-organized overview of the impacts of climate change and potential adaptation measures has been unavailable to date. Here we present a comprehensive review of climate-change impact studies that focused on the Thai water sector, based on a literature review of six sub-sectors: riverine hydrology, sediment erosion, coastal erosion, forest hydrology, agricultural hydrology, and urban hydrology. Our review examined the long-term availability of observational data, historical changes, projected changes in key variables, and the availability of economic assessments and their implications for adaptation actions. Although some basic hydrometeorological variables have been well monitored, specific historical changes due to climate change have seldom been detected. Furthermore, although numerous future projections have been proposed, the likely changes due to climate change remain unclear due to a general lack of systematic multi-model and multi-scenario assessments and limited spatiotemporal coverage of the study area. Several gaps in the research were identified, and ten research recommendations are presented. While the information contained herein contributes to state-of-the-art knowledge on the impact of climate change on the water sector in Thailand, it will also benefit other countries on the Indochina Peninsula with a similar climate.